Features of the value-semantic sphere of rescuers with different levels of professional socio-psychological adaptation - Koteneva A.V.; Kobzarev S.A. (Социальная психология и общество, 2019)
Currently, the research of personal resources of professional adaptation rescuers is socially significant, as extreme factors and activity conditions impose increased requirements for professionals, their professional and psychological training. The results of the empirical study of the features of adaptability, values and meanings of rescuers with different levels of professional socio-psychological adaptation are presented in the article. The survey involved 60 employees of the “Fire and rescue center”, all of them are men: the average age — 38.5 years; average experience — 11.7 years. The results showed that the professional adaptation success of rescuers is largely determined by the level of personal adaptive capacity, and its specific components — neuro-mental stability, communication skills, moral normativity. The material reward, spiritual satisfaction, achievements and social contacts were the most significant values for all specialists. However, the professional socio-psychological adaptation success increases if these values relate with the professional sphere of life. Existential values (acceptance of life and itself, ontological security, responsibility, death acceptance, the presence of crisis situation meaning and its concept) are the basis for both professional activities of rescuers and their adaptation to extreme conditions. At the same time, rescuers with a high level of professional socio-psychological adaptation have such characteristics as integration of life and death meanings in their crisis situation concept, acceptance of life changes, understanding of life as an opportunity to realize existential motives and meanings, ignoring death feelings and experiences.